arrange the first equation to x = y-5
sub replace the x in the second equation with that expression
2(y-5) - y = -7
2y - 10 - y = -7
y = -7 + 10
y = 3 , now let's put that back into x = y-5
x = 3 - 5
x = -2
so x = -2, y = 3
check in the first:
is -2 - (3) = -5 ? , yes!
in the second:
is 2(-2) - (3) = -7 ? , yes!
math - Solve the following system of linear equations using the matrix inverse ...
maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...
math - how do i solve this linear system using substitution or elimination -16x+...
Math - Solve the linear system by using elimination. 6x+y=39 -2x+y=-17
Math - x+3y=1 -5x+4y=-24 Solve the linear system by using elimination
Algebra - solving linear equations w/ substitution - The question in the book ...
Algebra I - How do you write a system of linear equations in two variables? ...
math - Create a linear system to model this situation. Then use substitution to...
Math - Solve the linear system by using elimination. 9x-4y=26 18x+7y=22
math - What is the linear system? 2x+2y=16 4x-6y=2 I am using elimination to ...